Pengaruh Return On Assets, Debt To Equity Ratio Dan Pertumbuhan Penjualan Terhadap Manajemen Laba Pada Perusahaan Industri Batubara Yang Terdaftar Di Bursa Efek Indonesia - Masmumah Sarmillah, Nur; Saraswati, Wiwik; Wulan Trifina, Butet (Jurnal GeoEkonomi, 2026)
This study aims to analyze the influence of Return on Assets (ROA), Debt to Equity Ratio (DER), and Sales Growth (SG) on Earnings Management in selected companies. The findings indicate that ROA has a significant negative effect on Earnings Management, suggesting that companies with higher financial performance tend to reduce earnings manipulation due to increased investor trust in transparent financial reporting. In contrast, DER shows no significant effect, implying that changes in capital structure or leverage levels do not significantly impact earnings management practices. Meanwhile, SG has a significant positive effect, indicating that companies with higher sales growth are more likely to engage in earnings management, potentially to maintain a positive corporate image and attract investors. Overall, the regression model explains 35.1% of the variation in Earnings Management, demonstrating that financial performance factors, particularly ROA and SG, play a crucial role in shaping earnings management practices. The model is statistically significant, as indicated by the F-statistic with a high level of significance.